Application of Solutions of Cerium Dioxide and Gadolinium Orthovanadate Nanosized Particles in Hypothermic Storage of Spirulina platensis Cell Culture - Hrechyshnikova, Mariia P.; Goloyad, Mikhail A.; Lipina, Olga V.; Falko, Oksana V.; Chizhevsky, Victor V. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 173